Investigating Cartoon Film Toward Student’s Listening Skill: Investigasi Film Kartun Terhadap Keterampilan Menyimak Siswa - Siti Danti (INGGARA (Jurnal Pendidikan Bahasa Inggris dan Bahasa Arab), 2023)
Listening is the process of making meaning from is heard, and as such, has a critical function for learning. Although students spend a large portion of class time of listening that must be explicity taught. Cartoon film is one of the media can be applied by a teacher as medium in teaching and learning process, especially teaching listening skill. In this study, the writer tried to investigate the cartoon film toward students listening skill for the first year of MA Keterampilan NW Pancor . The method that is used in this study is an experimental because the researcher investigated and analyzed the data. The population of the study is the whole classes of the first year students of MAK NW Pancor taken by claster sampling. Pre test and post test is used to get the data as instrument. The result showed that using the media in teaching and learning process is more effective to increase the students’ motivation and enthusiasm in doing learning process.